2000
DOI: 10.1159/000024343
|View full text |Cite
|
Sign up to set email alerts
|

IgE-Mediated Sensitization to Mould Allergens among Patients with Allergic Respiratory Diseases in a Desert Environment

Abstract: Background: The importance of fungal allergens in the development of allergic diseases in a desert environment is uncertain. This study evaluated the prevalence of IgE sensitization to moulds among patients with allergic respiratory diseases in Kuwait – a desert country. Methods: A total of 810 patients (male:female ratio 1.4) with a mean age of 32.3 years (range 2–76 years) with extrinsic asthma or allergic rhinitis were studied. Sera from the patients were tested by the CAP-RAST method for specific IgE to 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
2
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 22 publications
5
44
2
5
Order By: Relevance
“…Similar results were reported by Ezeamuzie et al [16], although their study was conducted in a desert area, whereas our study was conducted in a subtropical region characterized by high temperature and humidity. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results were reported by Ezeamuzie et al [16], although their study was conducted in a desert area, whereas our study was conducted in a subtropical region characterized by high temperature and humidity. …”
Section: Discussionsupporting
confidence: 91%
“…Exposure to allergenic fungi may lead to IgE-mediated allergic respiratory disease [16] and AD [9], yet few studies have examined fungal sensitization in Asian populations. Our study showed comparable findings with regard to age dependency of mold sensitization to those reported in the literature [16,17,18]. The sensitization pattern revealed that fungal allergy was extremely common among children with RAD, especially in those <10 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fungal allergens were the most common airborne fungi in many areas with similar climate within our region (20,21).…”
Section: Methodsmentioning
confidence: 91%
“…Only in the concentrations of Epicoccum were no significant differences between the sampling sites. Airborne spore concentrations greatly differ, a fact due to the variety of the vegetation existing in each region (Ballero et al, 1992;Eseamuzie et al, 2000). Awad (2005) reported that type of vegetation in the sampling area can affect the concentration and type of fungal taxa in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%